Integration of host resistance and fungicides reduced ascochyta blight pressure and minimised yield loss in field pea (Pisum sativum L.) in southern Ethiopia - Getachew Gudero Mengesha; Habtamu Terefe; Abu Jambo Yae; Asnake Abera Arato; Merihun Gimja Betire; Tamirat Samuel Shago; Zemenu Fentahun Bires; Biniyam Boraysho Borano; Shiferaw Mekonnen Abebe (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2022)
Ascochyta blight complex causes substantial yield losses and deteriorates seed quality of field pea worldwide. Field experiments were conducted to determine the effectiveness of an integrated approach consisting of host resistance and fungicides to reduce ascochyta blight progression and enhance yield performances of field pea for two seasons at Bonke and Chencha, Southern Ethiopia. Three field pea (Bursa, Burqitu and Tegegnech) varieties and three systemic (Carbonchlor, Matico and Othello-Top) fungicides, along with unsprayed controls, were arranged in a factorial randomised complete block design with three replications. Results showed that fungicide treated plots of each variety recorded the lowest progress rate, while control plots of Bursa, Burqitu and Tegegnech recorded the highest rate parameter (0.67, 0.60 and 0.451 units day−1), respectively at Bonke. Terminal mean severities were reduced by up to 24.6–43.7% and 20.1–43.7% due to fungicide applications over unsprayed plots at Chencha and Bonke, respectively. Moreover, triple applications of Othello-Top enhanced grain yield by 211% (Bursa), 204% (Burqitu) and 140% (Tegegnech) as compared to control plots at Bonke. A related pattern was noticed at Chencha areas. Economically, Burqitu with Othello-Top showed the highest net benefit and benefit–cost ratio of $2.35 × 103 ha−1 and 4.77 (Bonke) and 2.27 × 103 ha−1 and 3.76 (Chencha) in that order of presentation, followed by Matico, and found to be the most profitable management option due to monetary advantage; and it could be suggested for field pea growers.